2018
DOI: 10.1111/chso.12296
|View full text |Cite
|
Sign up to set email alerts
|

Counting Young Carers in Switzerland – A Study of Prevalence

Abstract: An online survey of children in school grades 4–9 (mostly aged 10–15) was conducted in order to determine the prevalence of young carers in Switzerland using a 2‐stage stratified sampling approach. 4082 respondents were drawn from 230 schools. A total of 3991 respondents were included in the analysis and of these 307 (7.7%) were identified as young carers. The population estimate of prevalence was 7.9 per cent. This suggests that there are around 38 400 young carers in school grades 4–9 in Switzerland. Extrapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 17 publications
6
68
0
5
Order By: Relevance
“…Many results according to gender differences, care recipients, nature and extent of caring activities provided by children and adolescents are in line with other study results , although direct comparisons are difficult due to different designs, sampling strategies, age groups and assessment instruments.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Many results according to gender differences, care recipients, nature and extent of caring activities provided by children and adolescents are in line with other study results , although direct comparisons are difficult due to different designs, sampling strategies, age groups and assessment instruments.…”
Section: Discussionsupporting
confidence: 84%
“…For German‐speaking countries, results of an Austrian survey of ten‐ to 14‐year‐old pupils (n = 7403), a Forsa survey of twelve‐ to 17‐year‐olds (n = 1005) and a recently published online survey from Switzerland of children aged 10–15 years (n = 3991) are available. In Austria, the prevalence of young carers is 4.5% , the Forsa survey shows a prevalence of 5% but has a comparatively small sample , and the Swiss study reports a prevalence of 7.7% . Further figures for Germany are missing.…”
Section: Introductionmentioning
confidence: 99%
“…These differing perspectives lead to varying estimates of the size of the young carer population (Joseph, Sempik, et al, ). The estimated prevalence of young carers in Europe ranges from 4.5% among Austrian children aged 10–14 years to 8% among UK children aged 11–18 years (Leu et al, ). A recent survey from England among children aged 11–12 and 14–15 years found that 7% of children were engaging in a high amount of caring activity and 3% were engaging in a very high amount (Joseph, Kendall, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…"[...] lms can help to make the children's and youth's perspective clearer, because it affects you. That's why we usually watch lms in our meetings for children's advocates [2]. There are lms on the Swedish Family Care Competence Centre's website, where children and youngsters tell their stories, making it lifelike and clear" (P6, R2, Sweden).…”
Section: Awareness Raisingmentioning
confidence: 99%
“…In families where one of the family members has a physical or mental health problem, children or adolescents are often involved in caregiving roles [1,2]. These young people are de ned in the literature as young carers (YCs), that is: children and young people under 18 years of age who provide or intend to provide care, assistance or support to another family member.…”
mentioning
confidence: 99%